Pengaruh Penambahan Daun Pisang Kering (Klaras) dan Air Leri Terhadap Produktivitas Jamur Merang (Volvariella volvaceae) yang Ditanam Pada Baglog - Kinasih, Pakarti Arum, Dra. Suparti, M.Si (2015)
Klaras is organic wastes dried banana leaves which has the main contentains in the form of hemicelluloses, so klaras expeted to be used as a planting medium merang mushroom. Leri water contains minerals, vitamin B1, B12 and nutrients which can be utilized as assitional nutrients to the growth of merang mushroom. The purpose of this study was to determine the effect of dried banana leaves and leri water on the productivity of merang mushroom grown on baglog. This study arranged in a completely randomized design (CRD) with two factors and thre replications. Factor 1 is klaras by weight: 125 grams (K1), 250 grams (K2), and 375 grams (K3). Factor 2 is leri water by volume: 50 ml (L1) and 100 ml (L2). Measured parameter is the fruit body weight and the amount of mushroom fruit body. Data were tested by analysis of variance 2 lanes. Based on analysis of variance showed that the addition of klaras media and water leri with different concentrations of influence on body weight and the amount of fruit merang mushroom edible merang mushroom fruit body. The best treatment for the body weight of fruit is K2L1 is 80,84 grams. While the lowes treatment is K0L1 is 61,67 grams. The best treatment for a number of fruiting bodies K2L1 is 6 pieces. While the lower treatment is K0L1 is 4 pieces.